The Effectiveness of Collaborative Learning with Gift Envelope Game Media on Statistics Learning Outcomes - Selly Minalasari; Hobri Hobri; Susi Setiawani (Pancaran Pendidikan, 2019)
This study aims to know the effectiveness of collaborative learning with gift envelope game media on statistic learning outcomes. Student learning outcomes are measured only on the subject of collection and presentation data. This research is pure experimental research with a posttest only control group design. The population of this study were students of class VII SMP Negeri 12 Jember and the sample was class VII B as the experimental class and class VII D as the control class. The hypothesis testing method used is T-Test (Independent Sample T-test). Based on the results of data analysis, the value of tcount = 5.993 ≥ ttable = 2.00665 or ρ-value = 0,000 < 0.025 at the first meeting, while at the second meeting tcount = 5.069  ≥ ttable =2.00324 or ρ-value = 0,000 < 0.025. Based on the results of these calculations it can be concluded that H0 is rejected and H1 is accepted which means collaborative learning with gift envelope game media is effective for student’s learning outcomes